Moderating Effects of Tolerance for Ambiguity and Risktaking Propensity on the Role Conflict-Perceived Performance Relationship: Evidence from Singapore Entrepreneurs - TEOH, Hai Yap (Institutional Knowledge at Singapore Management University, 1997)
This study investigates the effects of tolerance for ambiguity and risktaking propensity in mediating the relationships between role conflict and perceived performance among 70 entrepreneurs in small and medium-sized businesses in Singapore. Entrepreneurial activity has been widely recognized as a major factor driving Singapore's economic development. Further insights therefore can be gained by this study, which addresses the above issues from the perspective of Singaporean entrepreneurs. As founders of their enterprises, entrepreneurs are often involved with many aspects of activities that create a high potential for conflict, having to play multiple roles, coping with competing and conflicting demands, and overcoming or accommodating to constraints. Role conflict faced by the entrepreneur can impede the entrepreneur's ability to perform effectively. However, the relationship between role conflict and perceived performance is not direct. Many entrepreneurial decisions will also involve ambiguity, because these decisions result in actions that are innovative and original. As entrepreneurs, they will have a significantly greater capacity to tolerate ambiguity than managers have. This suggests that an entrepreneur's tolerance for ambiguity may be able to assist in dealing with, or to moderate, the adverse personal effects of role pressures generated by role conflict. Investigation into this is the thrust of the first part of this research. The literature on entrepreneurship has often portrayed the entrepreneur as a risk-taker with expectation of receiving a profit as reward for this risk-bearing. Many studies on risk-taking behavior among entrepreneurs are focused on the risk-profile of entrepreneurs, that is, whether entrepreneurs are decidedly more risk-taking than nonentrepreneurs. In this second part of research, the investigation examines whether the effects of role conflict on performance outcomes are tempered by the entrepreneur's risk-taking propensity. An entrepreneur with high risk-taking propensity is more likely to succeed in coping with uncertainty and minimizing role stress than one with low risk-taking propensity. Results indicate that Singaporean entrepreneurs higher on tolerance for ambiguity or in risk-taking propensity are better positioned to neutralize the effects of role stress in the entrepreneurial role, leading to better performance outcomes. The weaker interactive effects however could be explained by several constraining circumstances: the stringent control and omnipresence of the government in most businesses (Tan and Tay 1994); dominance of MNCs in key industries, and the domination of government-linked businesses in various services (Boey and Chiam-Lee 1994)--all of which are said to somewhat discourage risk-taking and uncertainty-bearing. Despite the small moderator effects, these findings should be of significance to practitioners, because they suggest that the examination of the relationship between role conflict and performance would be incomplete without also considering the moderating effects of tolerance for ambiguity and risk-taking propensity.